Evaluating Genetic Variability of Sorghum Mutant Lines Tolerant to Acid Soil - W. Puspitasari; S. Human; D. Wirnas; Trikoesoemaningtyas Trikoesoemaningtyas (PPIKSN-BATAN, 2012)
High rainfall in some parts in Indonesia causes soil become acidic. The main constraint of acid soil is phosphor (P) deficiency and aluminum (Al) toxicity which decrease plant productivity. To overcome this problem, it is important to develop a crop variety tolerant to such conditions. Sorghum is probably one of the potential crops to meet that objective. Sorghum has been reported to have wide adaptability to various agro-ecology and can be used as food and animal feed. Unfortunately, sorghum is not Indonesian origin so its genetic variability is still low. From previous breeding works with induced mutation, some promising mutant lines have been developed. These mutant lines were included in the experiment carried out in Tenjo with soil condition was classified as acid soil with pH 4.8 and exchangeable-Al content 2.43 me/100 g. The objectives of this experiment were to study the magnitude of genetic variability of agronomy and grain quality characters in sorghum in order to facilitate the breeding improvement of the species. Plant materials used in this study were ten genotypes, including 6 mutant lines and 4 control varieties. The randomized block design with three replications was used in the experiment. The genetic variabilities of agronomic and grain quality characters existed among genotypes, such as plant height, number of leaves, stalk diameter, biomass weight, panicle length, grain yield per plant, 100 seed weight and tannin content in the grain. The broad sense heritabilities of agronomic characters were estimated ranging from medium to high. Grain yield showed significantly positive correlation with agronomic characters observed, but it was negatively correlated with protein content. Received: 05 December 2011; Revised: 21 June 2012; Accepted: 02 July 2012